Validation of haplotype-specific extraction for separating a mitochondrial DNA model mixture and application to simulated casework. (July 2018) - Zander, Judith; Otremba, Petra; Nagy, Marion
Highlights: HSE and mtDNA analysis for short amplicon lengths was complete to 219 pg of total DNA input. HSE and the subsequent midi-mito assay proved to be stable against DNA degradation. HSE allows 10-fold-plus increase of a 5% minor component in a mixture. HSE of mtDNA mixtures was successfully validated for forensic casework. Abstract: Haplotype-specific extraction (HSE) is a new field of application for the separation of mitochondrial DNA (mtDNA) mixtures and is developed to identify the mtDNA haplotypes of the contributors subsequently by sequencing. Here we show the validation of HSE with an exemplary mitochondrial DNA mixture into its individual haplotypes according to our laboratory standards. These specify several critical areas of assay performance to be tested, such as sensitivity, robustness and mixture studies comprising varying proportions of their components, degraded samples and samples of different qualities and material. Wereport the successful and unambiguous analysis of the exemplary separated mitochondrial DNA mixture under various conditions as well as simulated casework samples, which manifest as mixed nucleotide calls at single base positions previously. Here we demonstrate that the HSE assay is high sensitive, stable against degradation and applicable in a wide range of sample qualities. Based on our findings from the validation study, we believe that this assay has great potential power and may be useful for distinguishing among the mtDNA of individuals and their geographical origin in mixed DNA samples.